2016
DOI: 10.1016/j.cyto.2016.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Predominance of Th1 response, increase of megakaryocytes and Kupffer cells are related to survival in Trypanosoma cruzi infected mice treated with Lycopodium clavatum

Abstract: We investigated the number of megakaryocytes, Kupffer cells and ratios of Th1/Th2 and Th1/Th17 cytokines in survival of mice infected with Y strain of Trypanosoma cruzi and treated with Lycopodium clavatum. In a blind, randomized and controlled assay, Swiss male mice, 8weeks-old, infected with 1400 trypomastigotes (Y strain) were divided into groups and treated with: GLy - Lycopodium clavatum dynamization13c and GCI - alcohol solution 7° GL (vehicle medicine). The treatment was offered two days before infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 13 publications
0
2
0
4
Order By: Relevance
“…In fact, in the work of Brustolin Aleixo et al [ 20 ], it was observed that the use of this plant, formulated in a dynamized way, resulted in immunoregulation and, consequently, neuronal protection in mice infected with T. cruzi . Although only one article has evaluated the neuroprotective potential, other studies have shown that the use of CL induces protection against T. cruzi infection, mainly by improving clinical signs and increasing the survival of infected animals [ 38 , 39 ]. The authors suggest that these findings are due to the ability of LC to induce immune homeostasis on behalf of the host.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in the work of Brustolin Aleixo et al [ 20 ], it was observed that the use of this plant, formulated in a dynamized way, resulted in immunoregulation and, consequently, neuronal protection in mice infected with T. cruzi . Although only one article has evaluated the neuroprotective potential, other studies have shown that the use of CL induces protection against T. cruzi infection, mainly by improving clinical signs and increasing the survival of infected animals [ 38 , 39 ]. The authors suggest that these findings are due to the ability of LC to induce immune homeostasis on behalf of the host.…”
Section: Discussionmentioning
confidence: 99%
“…O organoterápico, ao passar a informação de resposta de organismo sadio ao hospedeiro infectado, possivelmente modulou informações imunofisiológicas, que foram fornecidas de forma específica, nesse modelo experimental utilizado, reproduzindo a resposta de estado saudável ao hospedeiro através da homeostase, observado através de melhor morbidade e menor parasitemia. Esses e outros efeitos induzidos pelo organoterápico têm sido demonstrados por nosso grupo de pesquisa em publicações científicas (7,24,25). No entanto, a espécie utilizada para a preparação dos organoterápicos é muito sensível (10,25) e, com a utilização de modelo mais resistente, seria possível observar mais claramente o efeito equilibrado e benéfico do medicamento, refletido, também, na maior sobrevida de animais infectados por T. cruzi (7,24).…”
Section: Discussionunclassified
“…Esses e outros efeitos induzidos pelo organoterápico têm sido demonstrados por nosso grupo de pesquisa em publicações científicas (7,24,25). No entanto, a espécie utilizada para a preparação dos organoterápicos é muito sensível (10,25) e, com a utilização de modelo mais resistente, seria possível observar mais claramente o efeito equilibrado e benéfico do medicamento, refletido, também, na maior sobrevida de animais infectados por T. cruzi (7,24).…”
Section: Discussionunclassified
See 2 more Smart Citations